2014
DOI: 10.1017/s0950268813003452
|View full text |Cite
|
Sign up to set email alerts
|

A concept for routine emergency-care data-based syndromic surveillance in Europe

Abstract: We developed a syndromic surveillance (SyS) concept using emergency dispatch, ambulance and emergency-department data from different European countries. Based on an inventory of sub-national emergency data availability in 12 countries, we propose framework definitions for specific syndromes and a SyS system design. We tested the concept by retrospectively applying cumulative sum and spatio-temporal cluster analyses for the detection of local gastrointestinal outbreaks in four countries and comparing the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…3 Syndromic surveillance using ready-to-use data has also been explored, mainly in emergency rooms. [5][6][7] Few initiatives have used ambulance data 5,8,9,10 or ambulance dispatch centre data. 5,8,10,11 Ambulance dispatch centres could be an alternative source of readily available data to monitor the occurrence of severe respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…3 Syndromic surveillance using ready-to-use data has also been explored, mainly in emergency rooms. [5][6][7] Few initiatives have used ambulance data 5,8,9,10 or ambulance dispatch centre data. 5,8,10,11 Ambulance dispatch centres could be an alternative source of readily available data to monitor the occurrence of severe respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of syndromic surveillance in identifying or monitoring subnational infectious GI outbreaks is less clear. This has been explored in the literature previously [9][10][11][12] using either modelled or retrospectively identified case studies, with varying results. In England, a study using a synthesized cryptosporidiosis outbreak, found that the surveillance system would be unlikely to detect such an outbreak [12].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Syndromic surveillance is a process by which public health agencies, hospitals, medical professionals, and other organizations share, analyze, and query health and health-related data in near real time to make information on the health of communities available to public health and other officials for situational awareness, decision-making, and enhanced responses to hazardous events and disease outbreaks. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Syndromic surveillance is distinguished from other public health surveillance systems by the combination of several characteristics, including automated exchange of data originally created for other purposes from clinical electronic health information systems and other sources, the creation of defined syndromes based on words in clinic text notes and diagnostic and treatment information when available, and automated data scans to detect and display statistical anomalies and alert users to potential adverse health events. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although users and...…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Syndromic surveillance is distinguished from other public health surveillance systems by the combination of several characteristics, including automated exchange of data originally created for other purposes from clinical electronic health information systems and other sources, the creation of defined syndromes based on words in clinic text notes and diagnostic and treatment information when available, and automated data scans to detect and display statistical anomalies and alert users to potential adverse health events. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although users and researchers are still assessing the uses and limitations of the systems, 10,11 many health agencies find syndromic surveillance to be an important addition to their other surveillance systems. [1][2][3][4][5][6][7][8][9][10]…”
mentioning
confidence: 99%
See 1 more Smart Citation